Self-Force and Inertia Old Light on New Ideas - Lyle, Stephen; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The vast majority of particles in particle physics are today considered to be bound states of other particles. All forms of binding energy and kinetic energy in such a state have to be included in its inertial mass. This book revives the classical explanation for this in the case of electromagnetic interactions. But it is also a reminder of the many benefits of this classical understanding that are simply dropped in modern accounts of inertia. This is a book for the motivated student who feels it is useful to remember where our theories come from. There is also a comprehensive overview of the state of the art in particle physics.
and Guide -- Some Notions of Electromagnetism -- Electromagnetic Mass -- A Brief Excursion into General Relativity -- Momentum and Energy in the EM Fields of a Charge Dumbbell -- Self-Force for Transverse Linear Acceleration -- Self-Force for Axial Linear Acceleration -- Self-Force for Transverse Rotational Motion -- Self-Force for Longitudinal Rotational Motion -- Summary of Results -- Reconciling Energy- and Momentum-Derived EM Masses -- Rigidity in Relativity -- Mass in Elementary Particle Physics -- Summary and Conclusion.
Keywords: Physics; Physics; Optics and Electrodynamics; Classical and Quantum Gravitation, Relativity Theory; Particle and Nuclear Physics; Theoretical, Mathematical and Computational Physics